2016
DOI: 10.1096/fj.201600759rrr
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric kinesin‐2, together with kinesin‐1, steers vesicular acetylcholinesterase movements toward the synapse

Abstract: Acetylcholinesterase (AChE), which is implicated in the pathophysiology of neurological disorders, is distributed along the axon and enriched at the presynaptic basal lamina. It hydrolyses the neurotransmitter acetylcholine, which inhibits synaptic transmission. Aberrant AChE activity and ectopic axonal accumulation of the enzyme are associated with neurodegenerative disorders, such as Alzheimer's disease. The molecular mechanism that underlies AChE transport is still unclear. Here, we show that expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
1
21
2
Order By: Relevance
“…These vesicles predominantly move towards the synapse in axons. Although Kinesin-2 is also found to bind and transport vesicles containing Acetylcholinesterase in the same axon (Kulkarni et al, 2016), we observed that Rab4 does not mark them. Similarly, the post-Golgi vesicles carrying N-Cadherin and β-Catenin, which are known to associate with Kinesin-2 (Hirokawa et al, 2009), exclude Rab4.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These vesicles predominantly move towards the synapse in axons. Although Kinesin-2 is also found to bind and transport vesicles containing Acetylcholinesterase in the same axon (Kulkarni et al, 2016), we observed that Rab4 does not mark them. Similarly, the post-Golgi vesicles carrying N-Cadherin and β-Catenin, which are known to associate with Kinesin-2 (Hirokawa et al, 2009), exclude Rab4.…”
Section: Discussionmentioning
confidence: 60%
“…In a recent study, it was shown that combined activities of Kinesin-1 and 2 steers the AChE containing vesicles in the axon (Kulkarni et al, 2016). A simultaneous association of these two motors was suggested to induce longer runs of the AChE containing vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…While this kinesin could be kinesin-1 itself, it is also possible that an additional kinesin is involved in transporting outposts. The best candidates for such another kinesin would be kinesin-2 or kinesin-3, which co-transport some cargo with kinesin-1 (Guardia et al, 2016;Gumy et al, 2017;Hendricks et al, 2010;Kulkarni et al, 2017;Lim et al, 2017;Ruane et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Models of axonal transport for individual types of organelles have largely focused on one anterograde kinesin type. However, some transport mechanisms can employ more than one kinesin type ( Hendricks et al , 2010 ; Guardia et al , 2016 ; Kulkarni et al , 2017 ). For example, in Drosophila axons, there is evidence that kinesin-1 and kinesin-2 both influence the transport and distribution of acetylcholine (ACh) esterase vesicles ( Kulkarni et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%